State-religion relationships and human rights law: towards a right to religiously neutral governance - Temperman, Jeroen (Studies in religion, secular beliefs and human rights, 2010)
This book presents a human rights-based assessment of the various modes of statereligion identification and of the various forms of state practice that surround and characterize these different statereligion models. This book makes a case for the recognition of a state duty to remain impartial with respect to religion or belief in all regards so as to comply with peoples fundamental right to be governed, at all times, in a religiously neutral manner